Die einzige überlieferte Renaissance-Harfentabulatur in Deutschland: D-LEm I.191 (um 1540) - Schöning, Kateryna (Die Musikforschung, 2024)
The manuscript D-LEm I.191 is presented here for the first time as a unique surviving Renaissance harp tablature in Germany. The paper provides comprehensive research results on the origins of the tablature, as well as its performance, didactic and aesthetic contexts in the 16th century. The manuscript is also situated in the context of 19th century historicism, as an object in the collection of Carl Ferdinand Becker (1804–1877). D-LEm I.191 was written in Central Germany around 1540 as a practical supplement (exercitio) and continuation of Martin Agricola’s Musica instrumentalis 1529, with which it is bound together. It explains through a fundamentum the basic tuning and playing techniques and demonstrates the practical use of the harp, which Agricola represented only as a picture. Thus, D-LEm I.191 documents for the first time: (i) the application of the old German keyboard tablature to the Renaissance harp, (ii) the method of intabulation for this instrument, and (iii) the adaptation of the known song and dance repertoire to the idiom of a diatonic Renaissance harp. The manuscript provides a unique insight into the cultivation of this repertoire in the school, student and urban-bourgeois milieus.